AGILITY ORGANISASI PASCA ALIH JABATAN FUNGSIONAL (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2022)
The implementation of the transfer of functional positions aims to create ASN professionalism, a dynamic, agile bureaucratic structure and improve the efficiency and effectiveness of public service performance. In the implementation of functional transfers, there are still several obstacles in the process of adjusting the transfer of functional positions, both those faced by ASN and organizations. The purpose of this article is to describe post-transfer organizational agility with the research subject of the Ministry of State Apparatus Utilization and Bureaucratic Reform. The research method is a mixed method by combining descriptive analysis with qualitative and quantitative approaches. The implementation of functional shifts can be seen directly from the organizational restructuring in the Ministry of State Apparatus Utilization and Bureaucratic Reform which has implications for organizational agility which has an impact on traceability, dependability and organizational experience. Organizational restructuring at the Ministry of State Apparatus Utilization and Bureaucratic Reform brought a new work culture and new organizational behavior in the internal organization, a shorter command line eliminates many tasks and authorities and high demands so that the organization is able to transform more agilely which results in turbulence within internally. organizations and civil servants who are generally not ready to face organizational restructuring.